Effect of Time Since Smoking Cessation on Lung Cancer Incidence: An Occupational Cohort With 27 Follow-Up Years - Su, Zheng; Jia, Xin-Hua; Zhao, Fang-Hui; Zhou, Qing-Hua; Fan, Ya-Guang; Qiao, You-Lin (Frontiers in Oncology, 2022)
Background: This special cohort reveals the effect of smoking cessation in occupational miners exposed to radon and arsenic. Methods: A total of 9134 tin miners with at least 10 years of underground radon and arsenic exposure were enrolled beginning in 1992 and followed for up to 27 years. Detailed smoking information was collected at baseline, and information on smoking status was consecutively collected from 1992 to 1996. Cox proportional hazards model was used to explore the relationship between time since smoking cessation and lung cancer. Results: A total of 1324 lung cancer cases occurred in this cohort over 167,776 person-years of follow up. Among populations exposed to radon and arsenic, miners after quitting smoking for 10 years or more had almost halved their lung cancer risk [adjusted hazard ratio (HR) = 0.55, 95%CI: 0.38–0.79], compared with current smokers. Among miners after quitting smoking for 5 years or more, lung cancer incidence approximately halved (HR = 0.52, 95%CI: 0.30–0.92 ) for squamous cell lung carcinoma, while it showed no significant decline for adenocarcinoma (HR = 0.79, 95%CI: 0.34–1.85 ). Conclusion: Smoking cessation for 10 years or more halved lung cancer incidence among miners exposed to radon and arsenic, and the benefit was more pronounced among squamous cell lung carcinoma.